Salmonid heterosis for resistance to amoebic gill disease (AGD) - Maynard, BT; Taylor, RS; Kube, PD; Cook, MT; Elliott, NG (Aquaculture, 2016)
Amoebic gill disease (AGD) has been an economically significant problem for the Tasmanian Atlantic salmon Salmo salar aquaculture industry for over 25 years. More recently, AGD has emerged as a major issue in other growing regions. Freshwater bathing remains the most effective treatment, although progress with selective breeding has shown that there are genetic mechanisms for resistance to be exploited. In this study, we compared the AGD resistance of Atlantic salmon, brown trout ( Salmo trutta ), and their interspecies hybrid. Using 22 Atlantic salmon and 20 brown trout broodstock in a factorial mating design, populations of Atlantic salmon, brown trout, and each reciprocal hybrid were produced. All populations were transferred to sea cages at 15 months of age and subjected to natural, chronic AGD challenge under semi-commercial conditions for six months. Disease severity was monitored over four infection cycles and AGD resistance calculated using gill scoring, a previously reported, industry-standard measure of gross AGD pathology. While the Atlantic salmon population became infected and required freshwater bathing four times during the trial, both hybrids and brown trout became infected and required bathing only once. Heterosis for AGD resistance was significant, with hybrids displaying up to a 69% improvement over the mid-parent average and a 48% improvement over the best parent. The brown trout ♀ Atlantic salmon ♂ (TS) population exhibited the highest levels of AGD resistance throughout the study, which covered the rearing of animals up until 21 months of age. Over this period the TS hybrid performed comparably to Atlantic salmon for growth rate and survival. The Atlantic salmon brown trout hybrid represents a model for further exploitation to advance the understanding of AGD resistance in salmonids, and may provide options for commercial growers.